Мonodevelopment of agricultural territorial systems: their territorial structure transformation - SmochkoNataliіa (Human Geography Journal, 2020)
The article reveals a retrospective analysis of the concept of «agrarian territorial system» and clarifies the essence of the concept of "mono-agrarian territorial system". The features of their formation in the theory of social geography have been presented. It has been determined that the issue of research of agrarian territorial systems was actively paid attention by scientists of different branches of knowledge. However, the study of agricultural systems was carried out in the generalization of the behavior of the studied object to the process of monodevelopment. In this case, the digital expression of the process of monodevelopment as the dynamics of absolute data of a certain type, characterizing the highest level of generalization has been presented, as a rule, as an additional characteristic of the object of study. It has been proved that in the normative legal acts of Ukraine defining the essence of the concept of «rural area» there was a disordered heterogeneous, often contradictory conceptual and terminological apparatus. It is characterized by chaos and inconsistency in the process of its use in research and management. The development of rural areas due to the peculiarities of their development as monosystems of different hierarchical level has been considered. The development itself has been outlined as monodevelopment. It has been determined that any numerical characteristic of the territory is the starting point of a specific process of monodevelopment that takes place within it. Even without dynamic data, but comparing the starting points of the various processes of monodevelopment, we can assume how they proceed in the analysed area. Of great importance is the study of monoprocesses (generalized at the regional level) related to the use of natural resources of agricultural production, in particular the analysis of indicators of the value of agricultural products; the cost of agricultural products sold by enterprises; the number of employees in Ukraine in general and in agriculture, forestry and fisheries in particular; use of agricultural products. We proved that for full coverage of the characteristics of rural development is not enough to study the course of a single monoprotsesu within it, or several processes, but it is important to study them against the background of the territorial structure of agricultural systems that will make it possible to understand the nature of their development as mono process and identify features of formation agrarian territorial formations as monosystems. For the first time the category «monoagrarian locality» has been applied and its essence has been revealed.